The Impact of Digital Culture on the Understanding of Qur'anic Texts: A Study in Contemporary Exegesis - Sura Ahmed Bader, (Islamic Sciences Journal, 2025)
The world is witnessing profound digital transformations that have influenced various fields of knowledge and thought, including Qur’anic studies. This research aims to examine the impact of digital culture on shaping the methods of understanding Qur’anic texts within the framework of contemporary exegesis. It analyzes the interaction between modern technologies and religious awareness, addressing the role of digital media in facilitating access to exegesis sources and promoting community participation in religious dialogue. The study also highlights the challenges posed by the internet environment, such as superficial understanding and the spread of unmethodical interpretations. The research adopts a descriptive, analytical, and comparative approach to explore this phenomenon, seeking to clarify the relationship between digital culture and modern exegetical methodologies, while presenting a balanced view of both advantages and drawbacks.